Philosophical Literacy: Dialogue on a Pedagogical Experiment - McCourtie, Lena; Miller, Peter (Canadian Journal of Higher Education, 2017)
This paper seeks to contribute to the ongoing debate in universities about literacy, the link between writing and academic success, and writing in specific disciplines. It reports the major phases in the design and implementation of a team-taught curriculum which integrated two half courses in writing and philosophy. The major objective was to develop philosophical literacy among students as a groundwork for future humanities courses. The unifying motif was "dialogue" which facilitated the negotiation between two members of faculty with different areas of expertise, the concept of philosophy as dialogue, and the student-teacher relationship as dialogue. Comments are made about some of the difficulties and uncertainties which students experienced initially, as well as certain modifications which were made to the curriculum. The successful completion of a wide range of differentiated tasks and the major assignment, a complex argumentative research paper, indicated the extent to which students had achieved the goal of philosophical literacy. The experiment raised a number of challenging theoretical and pedagogical questions, some of which are answered in the final section of the paper, while others still need to be researched.